Vasculitis Associated with Parrot Bornavirus 4 Infection in a Rose-Crowned Parakeet (Pyrrhurarhodocephala). (August 2022) - Chénier, Sonia; DeLay, Josepha; Leacy, Alexander; Pham, Phuc H.; Susta, Leonardo
Summary: A 3-month-old, female rose-crowned parakeet ( Pyrrhura rhodocephala ) was found dead after a 24-h course of lethargy and passing blood-tinged faeces. Fine white streaks were seen in the pectoral muscles on necropsy. Microscopic examination revealed typical lesions of avian ganglioneuritis and vascular necrosis in the pectoral muscles, myocardium, kidneys, air sacs, adrenal glands, pancreas and thyroid gland. These lesions were characterized by mural fibrinoid necrosis of small and medium-calibre arteries and arterioles, associated with lymphoplasmacytic inflammation, necrosis, atrophy and fibrosis of the surrounding tissues. Parrot bornavirus (PaBV) nucleoprotein was demonstrated by immunohistochemistry in smooth muscle and endothelial cells of many vessels. An avian bornavirus was isolated from kidney tissue and its identity confirmed as PaBV-4 by sequencing and phylogenetic analysis. We postulate that the vascular lesions could have been immune-mediated and that PaBV-4 may have played a role in its pathogenesis.